Focusing Test Efforts while Servicing Large Systems - Czerwonka, Jacek (2007)
This paper presents an analysis of the challenges behind servicing Windows operating system, ideas behind our system of collecting and reporting change-related data, implementation details, and some of the results we were able to achieve with it. Above all, this paper will show how appropriately collected and applied data exposes an additional layer of detail which supplements testers’ own skills and experiences and allows for better understanding of testing required in the context of a specific code change.